Gouty panniculitis in a 68-year-old man: case report and review of the literature - Weberschock, Tanja; Gholam, Patrick; Hartschuh, Wolfgang; Hartmann, Martin (International journal of dermatology, 2010)
Gouty panniculitis is a very rare disease. To date, only eight patients have been reported. In each case, time to diagnosis was lengthy. We describe a 68-year-old man with a 6-month history of tender, erythematous plaques and nodules involving the anterior aspects of the legs
Gesehen am 17.10.2023